Kinetic and system bias as drivers of metabotropic glutamate receptor 5 allosteric modulator pharmacology. (1st May 2019) - Sengmany, Kathy; Hellyer, Shane D.; Albold, Sabine; Wang, Taide; Conn, P. Jeffrey; May, Lauren T.; Christopoulos, Arthur; Leach, Katie; Gregory, Karen J.
Abstract: Allosteric modulators of the metabotropic glutamate receptor subtype 5 (mGlu5 ) have been proposed as potential therapies for various CNS disorders. These ligands bind to sites distinct from the orthosteric (or endogenous) ligand, often with improved subtype selectivity and spatio-temporal control over receptor responses. We recently revealed that mGlu5 allosteric agonists and positive allosteric modulators exhibit biased agonism and/or modulation. To establish whether negative allosteric modulators (NAMs) engender similar bias, we rigorously characterized the pharmacology of eight diverse mGlu5 NAMs. Radioligand inhibition binding studies revealed novel modes of interaction with mGlu5 for select NAMs, with biphasic or incomplete inhibition of the radiolabeled NAM, [ 3 H]methoxy-PEPy. We assessed mGlu5 -mediated intracellular Ca 2+ (iCa 2+ ) mobilization and inositol phosphate (IP1 ) accumulation in HEK293A cells stably expressing low levels of mGlu5 (HEK293A-rat mGlu5 -low) and mouse embryonic cortical neurons. The apparent affinity of acetylenic NAMs, MPEP, MTEP and dipraglurant, was dependent on the signaling pathway measured, agonist used, and cell type (HEK293A-rat mGlu5 -low versus mouse cortical neurons). In contrast, the acetylenic partial NAM, M-5MPEP, and structurally distinct NAMs (VU0366248, VU0366058, fenobam), had similar affinity estimates irrespective of the assay or cellular background. Biased modulation was evident for VU0366248 in mouse cortical neurons where it was a NAM for DHPG-mediated iCa 2+ mobilization, but neutral with DHPG in IP1 accumulation assays. Overall, this study highlights the inherent complexity in mGlu5 NAM pharmacology that we hypothesize may influence interpretation when translating into preclinical models and beyond in the design and development of novel therapeutics for neuropsychiatric and neurological disorders. Highlights: mGlu5 negative allosteric modulators can stabilise distinct affinity states. mGlu5 NAM affinity is both context and orthosteric probe dependent. Biased mGlu5 modulation is evident at the level of cooperativity and affinity.